2017
DOI: 10.1002/suco.201600052
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of shear strength degradation of a reinforced concrete column subjected to cyclic loading

Abstract: The purpose of this study was to investigate the mechanism of shear strength degradation of a reinforced concrete (RC) member under cyclic loading. First, the shear failure after flexural yield of tension reinforcing bars of a RC column designed as bridge pier under cyclic loading was simulated by the method of three-dimensional rigid-body-spring-model (3D RBSM) and the shear strength degradation was quantitatively evaluated by a numerical approach. Afterward, based on the shear resistant mechanism, the degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…9 The bilinear elasto-plastic reinforcement model with kinematic strain hardening was used for steel reinforcement. Previous studies [10][11][12][13][14][15][16][17] are also referred to for modeling of the specimen. Figure 18 shows a comparison of the hysteretic curves of the column specimens between the experimental results (solid line) and the analytical results (dashed line).…”
Section: Analytical Resultsmentioning
confidence: 99%
“…9 The bilinear elasto-plastic reinforcement model with kinematic strain hardening was used for steel reinforcement. Previous studies [10][11][12][13][14][15][16][17] are also referred to for modeling of the specimen. Figure 18 shows a comparison of the hysteretic curves of the column specimens between the experimental results (solid line) and the analytical results (dashed line).…”
Section: Analytical Resultsmentioning
confidence: 99%
“…Moreover, their results confirmed that the initial shear strength of a RC column will degrade remarkably under cyclic load with the increasing displacement ductility, whereas will not be significantly affected under one-side repeated load. On the basis of this work, Fu et al (2017) attempted to explain the degradation mechanism of shear strength of a standard RC column discussed in the research conducted by Nakamura et al (2015). Combining the theory of beam and arch actions and 3-D RBSM numerical method, they developed a practical procedure to decouple the beam and arch actions, truss action and concrete contribution for beam action separately from the initial or residual shear strength at each displacement ductility.…”
Section: Research Backgroundmentioning
confidence: 99%
“…In this study, based on the research works of Nakamura et al (2015) and Fu et al (2017), the individual effect of structural factors on the degradation behavior of shear strength was separately evaluated, and meanwhile the corresponding effect mechanism was clearly explained by the analysis of beam and arch actions. Attributed to the reveal of the shear resistance mechanism for each structural factor, this study will contribute to discussion of more accurate degradation curves of concrete shear contribution, evaluation of the deformation capacity considering the mechanism and the practical improvement method of deformation capacity, all of which were useful knowledge in terms of the shear failure of RC member after flexural yielding under cyclic loads.…”
Section: Research Significancementioning
confidence: 99%
“…The rigid elements are discretized using the Voronoi diagram to represent the heterogeneity of concrete and eliminate bias in the initiation of crack direction and propagation. The model has been proven effective in simulating various concrete engineering problems such as cracking, localization, and failure behaviors of reinforced concrete members . The confining steel tube, on the other hand, is modeled using a nonlinear isoparametric shell element which can simulate the local buckling effects in the steel tube.…”
Section: Introductionmentioning
confidence: 99%
“…The model has been proven effective in simulating various concrete engineering problems such as cracking, localization, and failure behaviors of reinforced concrete members. 11,12 The confining steel tube, on the other hand, is modeled using a nonlinear isoparametric shell element which can simulate the local buckling effects in the steel tube. Surface-based interface elements predefined on RBSM surfaces in contact with shell elements provide the load-transfer interaction between RBSM and shell FEM.…”
mentioning
confidence: 99%